Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
first one,
12q^2+34q-28
divide whole thing by 2
6q^2+17q-14
use trial and error and get (2x+7)(3x-2)
factored out form is (2)(2x+7)(3x-2)
2.
divide by 3
6h^2+5h-6
trial and error and get (2x+3)(3x-2)
so the factored form is (3)(2x+2)(3x-2)
3. divide by 2
6p^2-11x-10
use trial and error and get (2x-5)(3x+2)
the factored out form is (2)(2x-5)(3x+2)
4.divide by 4
2z^2+5z-12
use trial and error and get (x+4)(2x-3)
the factored form is (4)(x+4)(2x-3)
to factor the basic thing is
ax^2+bx+c
b=x+y
ac=xy
solve for x and y
so exg 2z^2+5z-12
a=2
b=5
c=-12
2 times -12=-24
then factctor -24 and find factors that add up to 5
-1, 24
-2, 12
-3, 8
-4,6
now add
-1+24=23
-2+12=10
-3+8=5 check
-4+6=2
the numbers are -3 and 8
split it into such
2z^2+8z-3z-12
group (2z^2+8z)+(-3z-12)
undistribute using distributive property
ab+ac=a(b+c)
(2z)(z+4)+(-3)(z+4)
now reverse distribute again
((2z)+(-3))(z+4)
(2z-3)(z+4)
12q^2+34q-28
divide whole thing by 2
6q^2+17q-14
use trial and error and get (2x+7)(3x-2)
factored out form is (2)(2x+7)(3x-2)
2.
divide by 3
6h^2+5h-6
trial and error and get (2x+3)(3x-2)
so the factored form is (3)(2x+2)(3x-2)
3. divide by 2
6p^2-11x-10
use trial and error and get (2x-5)(3x+2)
the factored out form is (2)(2x-5)(3x+2)
4.divide by 4
2z^2+5z-12
use trial and error and get (x+4)(2x-3)
the factored form is (4)(x+4)(2x-3)
to factor the basic thing is
ax^2+bx+c
b=x+y
ac=xy
solve for x and y
so exg 2z^2+5z-12
a=2
b=5
c=-12
2 times -12=-24
then factctor -24 and find factors that add up to 5
-1, 24
-2, 12
-3, 8
-4,6
now add
-1+24=23
-2+12=10
-3+8=5 check
-4+6=2
the numbers are -3 and 8
split it into such
2z^2+8z-3z-12
group (2z^2+8z)+(-3z-12)
undistribute using distributive property
ab+ac=a(b+c)
(2z)(z+4)+(-3)(z+4)
now reverse distribute again
((2z)+(-3))(z+4)
(2z-3)(z+4)
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.